2006
DOI: 10.2166/wst.2006.416
|View full text |Cite
|
Sign up to set email alerts
|

Disc filtration for separation of flocs from a moving bed bio-film reactor

Abstract: A Discfilter with 10 and 18 microm filter openings, respectively, was placed in parallel to a flotation plant for separation of biological flocs from a post-denitrifying Kaldnes Moving Bed Process, the last treatment step at the municipal wastewater treatment plant at Sjöunda, Malmö, Sweden. The effluent concentrations from the 10 and 18 microm filter were 2-5 and 2-8 mg SS L(-1), respectively, which is comparable to, or better than, the flotation plant. Comparison with experiences from activated sludge plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The development of the Discfilter as a separation technique for suspended solids from the MBBR plant at the Sjölunda WWTP represents a good example on more recent process development work. Disc filtration in this application was initially tested and developed at the Sjölunda WWTP (Persson et al, 2006). With nominal pore size openings of either 10 or 18 µm approximately 5 mg SS/l, or less, could be achieved in the Discfilter effluent without preceding coagulation/flocculation.…”
Section: On-going Development and Future Workmentioning
confidence: 99%
“…The development of the Discfilter as a separation technique for suspended solids from the MBBR plant at the Sjölunda WWTP represents a good example on more recent process development work. Disc filtration in this application was initially tested and developed at the Sjölunda WWTP (Persson et al, 2006). With nominal pore size openings of either 10 or 18 µm approximately 5 mg SS/l, or less, could be achieved in the Discfilter effluent without preceding coagulation/flocculation.…”
Section: On-going Development and Future Workmentioning
confidence: 99%
“…Since 2005, research on and commercialization of the removal of suspended solids (SS) by microscreens with woven media (either Disc filters or Drum filters) downstream of an MBBR have taken place. 3,4 The examination of the system's flow requires a lot of time and effort when designing a sewer network traditionally. The design of a sewer system is extremely challenging because so many crucial criteria/checks must be met at once.…”
Section: Introductionmentioning
confidence: 99%
“…Both were then followed by a downflow fine sand filter as the second stage. The results of this innovative study demonstrated that the downflow second stage filter plays an integral role in achieving a turbidity of less than 0.5 NTU Persson et al (2006). evaluated disc filtration for the separation of flocs from a moving bed bio-film reactor.…”
mentioning
confidence: 94%